Fundamentals Of Microbial Degradation Of Spodumene - E. Ilgar (Society for Mining, Metallurgy & Exploration, 1989)
Biodegradation of spodumene by Asnergillus niger has been investigated. This organism oxidizes sucrose to citric and oxalic acids (in approximately 50-sot proportions) which degrade the spodumene mineral. The kinetic effects of leach variables on the dissolution of lithium were determined. The maximum theoretically attainable rate of lithium extraction was calculated for the effect of pulp density, to be V : 3.01 x 10 kg m sand the corresponding constant value, K = 12.47% pulp density. The apparent activation energy of lithium extraction vas found to be ^E = 20.3 kJ and frequency factor A = 5.66 x 10 s for S-spodumene leaching by synthetic -3 citric and oxalic acids (each in 0.05 kmol m-3 concentrations).